Modalverbet skulle i dansk og dets engelske æekvivalenter - Sobkowiak, Mikołaj (Folia Scandinavica Posnaniensia, 2007)
In this paper the semantic variants of the Danish modal verb skulle and their English equivalents are analysed. The semantic fields of skulle and its formal equivalents in English i.e. shall/should, overlap to a certain extent, which often causes translation difficulties. It is discussed what linguistic means one needs to resort to when translating Danish sentences with skulle into English. The variants are divided into 3 groups (epistemic, deontic and dynamic), the criterion of the division being what modality type they express.